The Efficiency Toolkit: A Subversive Manual - Kohashi, Andrea (Canadian Journal of Academic Librarianship / Revue canadienne de bibliothéconomie universitaire, 2020)
As libraries increasingly turn to automated systems to make materials more available, they inadvertently create less accessible collections. The Efficiency Toolkit is an artists’ book exploring the implications of automation and efficiency innovations in human work. Using this bookwork as a point of provocation, the difference between the accessibility and availability of library materials is highlighted and the desire for innovation and efficiency in the workplace is questioned.